Influence of motor skills on situational success in handball - Markovic, K.; Ristic, V.; Markovic, S. (FIS communications in Physical Education, Sport and Recreation, 2016)
The aim of this paper is to discover certain information related to the impact of motor characteristics on the success in situational plays in handball, based on the data from collected research. The analysis of 14 studies, in which the aim was to test the basic and specific motor activities of men's and women's handball players, as well as non-athletes with basic knowledge of handball (university students) of different ages, brought to the conclusion that the examined parameters have a great impact on the success in situational plays in the game of handball. During the effective implementation of a basic technical element in handball . the shot, explosive power and precision have the biggest role. This data can be of great use to coaches in planning and programming of the training process, but also in selection of young handball players. Motor characteristics, agility and explosive leg strength are the most important factors in completing defensive tasks. However, these characteristics cannot be taken as decisive parameters for the selection of players separately. It is necessary to develop a complete motor status of players, with greater emphasis on motor characteristics that prevail in solving situational tasks of the game.